2013
DOI: 10.1080/09540121.2013.772273
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to dropping out from and returning to HIV treatment in an inner city primary care HIV clinic in the United States

Abstract: Although advances in pharmacotherapy have enabled people living with HIV/AIDS to live longer, fuller lives, some leave medical care, resulting in sub-optimal treatment and increased health risk to themselves and others. Forty-one patients who dropped out of an urban, publically funded primary care HIV clinic were contacted and encouraged by outreach staff to return. Participants were interviewed within two weeks of returning, and themes associated with dropping out and returning were elicited and content analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 16 publications
1
60
2
1
Order By: Relevance
“…Although we did not single out depression in this study, with the majority of the patients being diagnosed with depression, it was interesting to see that this group still had an increased odds of being optimally retained in care compared to their counterparts. This contradicts other studies that suggest that PLWH with mental health problems have much higher risks of missing clinic appointments or completely dropping out of care (Blashill, Perry, & Safren, 2011;Pecoraro et al, 2013). One explanation why there were higher rates of retention among those living with a comorbid condition is that these individuals may have had better control of their comorbid condition which in turn led to better retention in care.…”
Section: Discussioncontrasting
confidence: 65%
“…Although we did not single out depression in this study, with the majority of the patients being diagnosed with depression, it was interesting to see that this group still had an increased odds of being optimally retained in care compared to their counterparts. This contradicts other studies that suggest that PLWH with mental health problems have much higher risks of missing clinic appointments or completely dropping out of care (Blashill, Perry, & Safren, 2011;Pecoraro et al, 2013). One explanation why there were higher rates of retention among those living with a comorbid condition is that these individuals may have had better control of their comorbid condition which in turn led to better retention in care.…”
Section: Discussioncontrasting
confidence: 65%
“…14,[16][17][18][19] However, despite this finding, we found that, compared with women in care, both seekers and nonseekers were no more likely to perceive lack of health insurance as a barrier to care. Although prior studies have found drug use to be associated with poor engagement in care, 14,16,19,[21][22][23][24][25] we found that, compared with women in care, only non-seekers were more likely to report high-risk drug use and sexual behaviors. As this subgroup was less likely to report transportation as a barrier to care and was no more likely to report other structural barriers to care as women in care, our findings suggest that this subgroup of women may not report barriers because they are not actively seeking HIV medical care.…”
Section: Discussioncontrasting
confidence: 54%
“…Consequently, they are at high risk for poor health outcomes and for transmitting HIV to others. [4][5][6][7][8][9][10] Although prior studies have identified numerous factors associated with poor engagement in care (e.g., lack of transportation [11][12][13] and health insurance, [14][15][16][17][18][19] caregiving responsibilities, 13,20 depression, 13,16,21 and substance use 14,16,19,[21][22][23][24][25], these studies have been limited in two important respects. First, many have viewed those who are not engaged in care as a single, homogenous group, failing to recognize potentially nuanced differences among women that may help to inform the development of targeted interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Depression and substance use have been shown to negatively impact engagement and adherence in other cultures (e.g., inner-city US, Pecoraro et al, 2013), but few studies have examined attrition in the RF. In a prior St. Petersburg study (Pecoraro et al, 2014), EIC and LTC focus groups identified structural barriers: stigma/discrimination; problems with providers and access; and individual barriers: employment/caring for dependents; inaccurate beliefs about ART (only LTCs); side-effects; substance use (LTCs, present; EICs, past); and depression.…”
Section: Introductionmentioning
confidence: 99%